Perilaku Informasi Perpustakaan Dalam Pelayanan di Perpustakaan Universitas Islam Sumatera Utara - Franindya Purwaningtyas; Siti Pardiani Tanjung; Ineke Mayliningrum; Juni Ervina Sari; Siti Masitoh (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
In this study, library users were used as a source and the survey subjects were information seeking behavior at the UISU Medan Library lending and borrowing service, which also included the initiation, chaining, tracking, sorting, monitoring, selection and confirmation phases as well as the termination phases such as restrictions and occupancy factors. The purpose of this research is to find out how users search for information. The method used in this study is a qualitative method in which the collected data is compiled and analyzed. With this method, user behavior in the process of searching for information at the UISU Medan library loan service is described and analyzed. The results of the study show that the search for information in the UISU library is very flexible due to the different scope and research objectives and the information needs of each user of the UISU library. In the UISU library lending service, it is necessary to renew the user's ability to search for information, so that readers' views of various sources of information and information retrieval are better and more accurate. Keywords: source of information sea